State of exception, COVID-19 and fundamental rights - Figueroa Gutarra, Edwin (2020)
This study analyzes the social context of the State of Exception. COVID-19 have posed challenges to concepts such as social confinement, isolation and social mobility, limiting the ability to exercise Fundamental Rights. Finally, the standards of the Interamerican Human Rights systems are analyzed to adapt the interpretation of fundamental rights to comply with the provisions in the pandemic context.